2010
DOI: 10.1111/j.1365-2303.2010.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

Atypical squamous cells and low-grade squamous intraepithelial lesion in cervical cytology: cytohistological correlation and implication for management in a low-resource setting

Abstract: In a low-resource setting where human papillomavirus testing is unaffordable, the threshold for colposcopic referral and follow-up histology should be ASC rather than SIL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…CIN 3 and invasive squamous carcinomas were seen in 5.9 and 1.4%, respectively, of cases of atypical squamous cell, and these were not seen in low-grade squamous intraepithelial lesion. The authors demonstrated results similar to ours regarding the finding of high-grade lesions [18]. …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…CIN 3 and invasive squamous carcinomas were seen in 5.9 and 1.4%, respectively, of cases of atypical squamous cell, and these were not seen in low-grade squamous intraepithelial lesion. The authors demonstrated results similar to ours regarding the finding of high-grade lesions [18]. …”
Section: Discussionsupporting
confidence: 84%
“…Comparing our results with those of other resource-poor countries, Gupta et al [18], in India, suggested that, in a low-resource setting, HPV testing is unaffordable. They performed an audit of all cervical smears reported as atypical squamous cells and low-grade squamous intraepithelial lesions in order to determine their histological follow-up to define the threshold for colposcopic referral.…”
Section: Discussionsupporting
confidence: 70%
“…The ALTS study demonstrated the value of subcategorizing ASC‐US and ASC‐H with 41% of ASC‐H cases having underlying high‐grade intraepithelial lesion (HSIL) as compared to 12% in ASC‐US cases 3. Other studies have also confirmed the significance of subtyping ASC cases into ASC‐H 4–9. The majority of the previous studies are on conventional cervical smears.…”
mentioning
confidence: 85%
“…Data in the literature suggests that ASC-H and B-HG are associated with a higher prevalence of clinically significant cervical lesions compared with ASC-US and B-NOS. [4][5][6][7][8] In spite of proposed changes to UK terminology suggested by the British Society for Clinical Cytology (BSCC) in 2008, 9 the terminology currently in use in the National Health Service Cervical Screening Programme (NHSCSP) 10 does not support the use of B-HG and allows for koilocytosis with equivocal nuclear changes to be included in the BNC rather than a mild dyskaryosis category, which is otherwise equivalent to a low-grade squamous intraepithelial lesion (LSIL). This reflects the view that koilocytosis may indicate low-risk HPV infection, which may be transient and is not usually associated with high-grade cervical intraepithelial neoplasia (CIN).…”
Section: Human Papillomvirus; Low-grade Cytology Hpv Triage; Liquid-bmentioning
confidence: 99%
“…These categories are equivalent to BNC in squamous cells, not otherwise specified (B‐NOS) and BNC, high‐grade dyskaryosis cannot be excluded (B‐HG) in the UK. Data in the literature suggests that ASC‐H and B‐HG are associated with a higher prevalence of clinically significant cervical lesions compared with ASC‐US and B‐NOS 4–8 . In spite of proposed changes to UK terminology suggested by the British Society for Clinical Cytology (BSCC) in 2008, 9 the terminology currently in use in the National Health Service Cervical Screening Programme (NHSCSP) 10 does not support the use of B‐HG and allows for koilocytosis with equivocal nuclear changes to be included in the BNC rather than a mild dyskaryosis category, which is otherwise equivalent to a low‐grade squamous intraepithelial lesion (LSIL).…”
mentioning
confidence: 99%